Gastrointestinal manifestations in systemic lupus erythematosus. (November 2016) - Fawzy, M; Edrees, A; Okasha, H; El Ashmaui, A; Ragab, G
Systemic lupus erythematosus (SLE) is an autoimmune disorder characterized by multisystem involvement, including the gastrointestinal (GI) tract. There is a significant variation in the clinical presentation and severity of GI disorders. When GI symptoms present as the initial manifestation of SLE, there is likely to be a delay in the diagnosis. The cause of these GI manifestations in SLE may be the disease, or the side effects of medications, or infections. In this study we investigated the GI manifestations in a group of SLE patients. Our study was conducted on 40 SLE patients and 30 healthy controls to assess the prevalence of GI symptoms in SLE patients. The prevalence of gastrointestinal manifestations in our study was 42.5%. GI manifestations in our SLE patients were: acute abdominal pain (due to pleurisy and peritonitis), 6%; diffuse abdominal pain, 23.5%; epigastric pain, 29%; epigastric pain with vomiting, 23.5%; epigastric pain with chronic constipation, 6%; chronic constipation, 6%; and diffuse abdominal pain with bleeding per rectum, 6%. In our study, we found a higher incidence of Giardia infestation in SLE patients than in healthy controls, and 10% of these patients were asymptomatic. There was more Giardia infestation in patients with GI symptoms as compared with patients with no GI symptoms, with a P value of 0.009. In our study SLE patients with GI symptoms had a peak systolic velocity (cm/s) with a mean of 108.4 ± 32.1 standard deviation (SD) in the celiac Doppler study. Patients without GI symptoms had a peak systolic velocity with a mean of 111.9 ± 37.7 SD, meaning that our patients mostly had no evidence of celiac trunk stenosis, but there was significant difference between SLE patients without GI symptoms and controls, as the mean was higher in SLE patients than in the controls. Also, the celiac end diastolic velocity was higher in both groups of SLE patients with GI symptoms and those without GI symptoms, compared to controls.